2008
DOI: 10.1115/1.3005165
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Calibration Method on Tekscan Sensor Accuracy

Abstract: Tekscan pressure sensors are used in biomechanics research to measure joint contact loads. While the overall accuracy of these sensors has been reported previously, the effects of different calibration algorithms on sensor accuracy have not been compared. The objectives of this validation study were to determine the most appropriate calibration method supplied in the Tekscan program software and to compare its accuracy to the accuracy obtained with two user-defined calibration protocols. We evaluated the calib… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
94
0

Year Published

2011
2011
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 150 publications
(97 citation statements)
references
References 11 publications
0
94
0
Order By: Relevance
“…2). The area of the matrix was 27 mm 9 38 mm and was calibrated at 20% and 80% of the estimated ankle loading of 750 N [6]. The area of the matrix was 26.7 mm 9 38.4 mm, which consisted of 1472 sensels (sensing elements) with spatial resolution of 0.8 mm 9 0.8 mm.…”
Section: Contact Mechanicsmentioning
confidence: 99%
“…2). The area of the matrix was 27 mm 9 38 mm and was calibrated at 20% and 80% of the estimated ankle loading of 750 N [6]. The area of the matrix was 26.7 mm 9 38.4 mm, which consisted of 1472 sensels (sensing elements) with spatial resolution of 0.8 mm 9 0.8 mm.…”
Section: Contact Mechanicsmentioning
confidence: 99%
“…Each sensor was calibrated under the same environmental conditions as those registered during the in vitro experiments. This calibration is more precise 20 than the manufacturer's process, particularly when used at a locally limited area under full saturation pressure. 21 The anterior and posterior aspects of the menisci (alH ¼ anterolateral horn; plH ¼ posterolateral horn; amH ¼ anteromedial horn; pmH ¼ posteromedial horn; Fig.…”
Section: Measuring Devicesmentioning
confidence: 99%
“…Furthermore, the accuracy of the Tekscan System may be lower than reported in dynamic loading situations because of the effects of shear loads, loading between curved surfaces or small contact areas. Sensor output and output variability depend on the stiffness of the contact materials (Brimacombe et al, 2009). Lou et al (1998) found the sensor to be sensitive to surface conditions, loading speeds and temperature, and rated the F-Scan Tekscan sensor system unsuitable for hard surface contact.…”
Section: Discussionmentioning
confidence: 99%
“…The measuring system was con nected via a 10-m cable and a 16-bit receiver card to a microcomputer with the corresponding pressure and force measurement software program. To obtain meaningful measurements, the Tekscan sensors must be calibrated to the anticipated pressure range (Brimacombe et al, 2009). Therefore, before obtaining any force measurements, each sensor was individually calibrated with the previously recorded weight borne by the hind limbs with the horse standing square.…”
Section: Measurement Of the Force Of A Kickmentioning
confidence: 99%